2019
DOI: 10.3389/fpsyg.2019.01596
|View full text |Cite
|
Sign up to set email alerts
|

Principles, Approaches and Challenges of Applying Big Data in Safety Psychology Research

Abstract: Big data is now widely used in many fields and is also widely applied to the integration of disciplines. Traditional methods of safety psychology are not well suited for analyzing psychological states, especially in the management of human factors in industrial production. Also, big data now becomes a new way to excavate related insight by analyzing a large amount of psychological data. So, this paper is to propose the concept of big data of safety psychology (BDSP) and to illustrate the challenges of applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In addition, in this study, it was found that information quality has a significantly higher impact on trust than satisfaction. It is also found from previous studies that data security is a well-known and challenging issue (Dawson and Thomson, 2018;Kang et al, 2019). Therefore, the risk arising from information quality is a key factor in choosing a cloud financial and accounting system (Demirkan et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, in this study, it was found that information quality has a significantly higher impact on trust than satisfaction. It is also found from previous studies that data security is a well-known and challenging issue (Dawson and Thomson, 2018;Kang et al, 2019). Therefore, the risk arising from information quality is a key factor in choosing a cloud financial and accounting system (Demirkan et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Kang et al [8]. proposed the concept of massive information on security psychology (BDSP) and aimed at demonstrating the challenges of applying big data in security brain research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these, Kang et al (2019) introduced the BDSP concept to hold how big data adoption and utilization may positively affect workplace health and safety. They define BDSP as "structured, semi-structured, and unstructured datasets formed by psychological index parameters and behavior, which provide potential and valuable psychological knowledge and rules to solve the psychological issues related to safety with the help of big data technology" (p. 3).…”
Section: Big Data Of Whatever Psychologymentioning
confidence: 99%
“…This commentary builds upon the recent theoretical paper by Kang et al (2019) to advance the debate currently going on about psychology and big data. The aim is to discuss the feasibility of extending the conceptualization proposed by the authors-i.e., Big Data of Safety Psychology (BDSP)-to other branches of psychology going beyond the only safety domain, ultimately pointing out a big data of whatever psychology scenario.…”
Section: Introductionmentioning
confidence: 99%